The Relationship of Self Regulation with Academic Procrastination of Students - Desi Saputri; Asmidir Ilyas; Zadrian Ardi (Jurnal Neo Konseling, 2020)
Academic procrastination is the tendency of students to postpone and complete academic assignments so that it adversely affects learning outcomes in school. In this case one of the factors that influences academic procrastination is students' self regulation. By having good self regulation, students can manage and manage themselves in completing academic tasks. But the findings in the field are still the existence of students who carry out academic procrastination, and tend to prioritize more enjoyable activities. This study aims to look at the picture of academic procrastination and self regulation of students and determine the relationship between self regulation and academic procrastination of students at SMA Negeri 5 Padang. This research is a descriptive correlational study. With a sample of 279 students selected using the proportional stratifed random sampling technique. Data collection uses self-regulation and academic procrastination questionnaires with a Likert scale model. The results revealed (1) students' self regulation in general was in the high category of 177 people with 63%, (2) the academic procrastination of students was mostly in the low category of 147 people with 53%, (3) there was a negative relationship significant between self regulation and academic procrastination of students of SMA Negeri 5 Padang of -0,706 with a significant value of 0,000. The findings of this study can be a reference for BK teachers in making programs to provide BK services to students.